Trans-boundary atmospheric pollution – concerns and approaches in Malaysia - Azizan Ahmad,; Hanim Kamaruddin, (Environmental Management Society, Malaysia, 2001)
Only relatively recently, Malaysia has never really regarded the problems and effects of trans-boundary atmospheric pollution or better known as haze as serious or needed any urgent attention. However, with the phenomenon of haze in 1997 that had engulfed and triggered possibly the worst condition of haze in Malaysia, Singapore and Indonesia had only confirmed the need to take immediate responses against this environmental catastrophe. The cause of the 1997 haze was due to the forest fires in Indonesia mainly related to the use and clearance of forest for new development. The concerned governments have recognized that the haze had caused harm to human life and health and the environment not only to Indonesia but also to Malaysia and Singapore. Various regional agreements and collaborations have been agreed upon by the concerned states in the effected areas of Southeast Asia. At national level, Malaysia had taken all possible measures to reduce the effect of haze, among others, by implementing and activating the National Haze Action Plan. Other methods include increasing public awareness and education campaigns, disseminating information regarding the Air Pollution Index (API) readings and had also attempted to reduce and control the haze by “cloud seeding”. Stricter enforcement of the law had also been carried out against open burning. In addition, two new provisions have been introduced in the Environmental Quality Act 1974 as a result of the 1997-haze crisis. Several years have lapsed since the 1997 haze. However, in early March 2000, reports have indicated increasing number of forest fires in the Riau province of Sumatera. Hence, the incidence of haze was repeating itself in Malaysia and Singapore. Even though the condition is constantly improving, the concern towards the haze remains. This article reviews the non-legal and legal approaches taken by Malaysia and the effectiveness of these management strategies in curbing the incident of transboundary atmospheric pollution